Human Resource Practices and Employee Retention in Manufacturing Industry - Leong Wai Kin; Nurazwa Ahmad; Nor Kamariah Kamaruddin; Tengku Nur Azila Raja Mamat (Research in Management of Technology and Business, 2022)
Manufacturing companies encountered the challenge to retain and hire the most talented workforce to maintain market leadership. Besides, the voluntary attrition rate in the year 2019 was 6.5% and manufacturing sectors in Malaysia had the highest turnover rate, which is 24%. A comprehensive understanding of the relationship between employee retention and human resource practices will help organizations to construct better verdicts to achieve their business goals. This study aims to determine the level of employee retention, human resource practices, and examine the relationship between human resource practice and employee retention. This study was conducted among 284 employees from manufacturing companies in Selangor. Quantitative approach had been employed and online data collection were sent by email. Descriptive analysis and Spearman correlation analysis were engaged to achieve the objectives. The results indicated there is a high level of employee retention and human resource practices among the manufacturing employees. The findings also showed a significant positive correlation between employee retention and human resource practices, thus supporting all the hypotheses. These results will give better guidance to the manufacturing organization and future researchers. It also helps the management in better understanding on how to manage human resources well, while also considering the employee retention scale.